1993
DOI: 10.1200/jco.1993.11.9.1652
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of cyclosporine as a chemotherapy-resistance modifier in acute leukemia.

Abstract: High doses of CsA, which achieve blood concentrations capable of reversing P-glycoprotein-mediated anthracycline resistance in vitro, can be incorporated into induction regimens with acceptable nonhematologic toxicity. Transient hyperbilirubinemia occurs commonly with CsA administration and may alter daunorubicin pharmacokinetics. Recommended doses of CsA for phase II and III trials are a load of 6 mg/kg and CI of 16 mg/kg/d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(126 citation statements)
references
References 26 publications
0
123
0
3
Order By: Relevance
“…94 To improve treatment efficacy, combination of MDR1 inhibitors with specific drugs have been tested, showing notably encouraging results in term of overall survival in patients with AML. 22,9597 Most of these studies used first or second generation inhibitors. The use of much more specific third or upcoming fourth generation inhibitors could allow to improve these results and decrease toxicities associated with combination treatments.…”
Section: Introductionmentioning
confidence: 99%
“…94 To improve treatment efficacy, combination of MDR1 inhibitors with specific drugs have been tested, showing notably encouraging results in term of overall survival in patients with AML. 22,9597 Most of these studies used first or second generation inhibitors. The use of much more specific third or upcoming fourth generation inhibitors could allow to improve these results and decrease toxicities associated with combination treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in experimental animals (Nozue et al, 1993) and in humans (List et al, 1993) showed an association between hypomagnesaemia and the use of cyclosporin, possibly due to intracellular migration. Furthermore, hypomagnesaemia was reported to be associated with chemotherapy with cisplatin (Fossa et al, 1995), as well as a combination of cisplatin and 5-¯uorouracil (Evans et al, 1995), owing to increased losses of minerals with urine.…”
Section: Micronutrient De®cienciesmentioning
confidence: 99%
“…Phase I studies showed that both CsA and PSC 833 increased the area under the curves of etoposide, daunorubicin and doxorubicin. [50][51][52][53][54] However, a disadvantage of this increase in plasma levels is that drug doses should be reduced to limit the toxic sideeffects. Side-effects have been reported at the clinically achievable concentrations of PSC 833, CsA and Vp used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…55 The toxicity of CsA was milder, mainly resulting in myelosuppression and hypomagnesemia. 52,56,57 The lowest toxicities were reported for PSC 833 and included ataxia and intestinal neuropathy.…”
Section: Discussionmentioning
confidence: 99%